“Check Your Face(Book) on Page…”: Unpacking the Pedagogical Potentialities of English Teachers’ Wall Posts - Al Ryanne Gabonada Gatcho; Bonjovi Hassan Hajan (Lingua Cultura, 2019)
This research aimed to show an increasingly digitized world where technology continued to revolutionize how human interactions were enacted, so the teachers must transcend educational boundaries to provide quality education that was responsive to the needs of the 21st-century society. This research examined the Facebook wall postings of selected English senior high school teachers in Metro Manila, Philippines. Using thematic analysis, the research investigated and analyzes these Facebook posts (wall posts) to identify whether teachers; (1) could potentially initiate communication (student-teacher interaction, in particular online/via Facebook) and (2) used such social network site for academic/instructional purposes. Main themes identify in the student-teacher interaction are gratitude and appreciation, longing, interest, and status, while those that are recorded in the teachers’ wall posts are announcements, student activity documentation, and extra-curricular activities. The findings of this research help establish the importance of technology integration in the field of teaching and learning English as a second language. Moreover, the research is pivotal in the resurfacing of constructivism in education and the emergence of new communication norms brought about by technological innovations.